A Cross-national Analysis of Economic Gender Equity and Welfare State Development - Vicky Lovell (Luxembourg Income Study (LIS), 1999)
Economic gender equity exists when women and men equitably share economic activity, both within and outside markets, and economic compensation, although they may combine labor market and domestic work differently and receive compensation from different sources. This analysis uses an Index of Economic Gender Equity to compare women's and men's relative economic well-being in eleven industrialized democracies. Equity increases when leftist and women's political representation is stronger and under conditions of higher labor demand and rising labor costs. Women's educational achievement does not influence women's relative economic standing, but the ratio of women's to men's levels of education does. Although each country's cultural environment flavors its gender relations, political, economic and social institutions can be effective in advancing the gender equity of economic relations.
Keywords: 330; Arbeitsmarkt; Hausarbeit; Bildungschancen; OECD-Staaten; Gleichberechtigung